Long-term prognosis of patients with Takotsubo syndrome - Templin-Ghadri, Jelena-Rima; Kato, Ken; Cammann, Victoria L.; Gili, Sebastiano; Jurisic, Stjepan; Di Vece, Davide; Candreva, Alessandro; Ding, Katharina J.; Micek, Jozef; Szawan, Konrad A.; Bacchi, Beatrice; Bianchi, Rahel; et al. (Journal of the American College of Cardiology, 2018)
Takotsubo syndrome; acute coronary syndrome; broken heart syndrome; classification; outcome; stress factor